Importance of testing stapled rectal anastomoses with air - (:unkn) unknown (My University, 1993)
OBJECTIVE: To compare the air test (insufflation of air through the anus after the peritoneal cavity has been filled with saline) and the completeness of doughnuts as indicators of the integrity of stapled rectal anastomoses. DESIGN: Prospective open study. SETTING: Marmara University Hospital, Istanbul, Turkey. SUBJECTS: 23 patients with sigmoid and rectal carcinoma. MAIN OUTCOME MEASURES: Correlation between positive air test, completeness of doughnuts, and clinical anastomotic breakdown. RESULTS: Two patients were withdrawn (one had a handsewn anastomosis and in one the air test was omitted). Five patients had positive air tests, and in four of these the doughnuts were complete. The leaks were repaired with additional sutures in three patients, and two were given covering colostomies. There was only one clinical anastomotic breakdown. CONCLUSION: The air test enabled the surgeon to repair or protect five anastomoses (24%). The completeness of the doughnuts was an reliable test of anastomotic integrity.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Aged, 80 and over; Male; Reoperation; Prospective Studies; Rectum; Suture Techniques; Anastomosis, Surgical; Air; Colostomy; Insufflation; Intraoperative Care; Rectal Neoplasms; Sigmoid Neoplasms; Surgical Staplers